Gymnodactylus caspius insularis ssp. n. (Reptilia, Sauna) — новый подвид каспийского геккона с острова Вульф в Каспийском море - Ахмедов, М.И.; Щербак, Н.Н. (Вестник зоологии, 1978)
The articles deals with a description of the new subspecies Gymnodactylus caspius insularis from the Vulf island (the Bay of Baku, the Caspian Sea) characterized by the absence in all the individuals of broad suture between the first nair of mandibular scutellum behind the genial one.